Palm Oil Employee Performance: Are Knowledge Sharing, Learning Organization, And Work-Life Balance The Issues? - Enny Noegraheni Hindarwati; Tinjung Desy Nursanti; Laksmi Sito Dwi Irvianti; Kevin Kevin; Masruroh Masruroh (Jurnal Ilmu Manajemen dan Ekonomika, 2022)
The purpose of this study was to find out the impact of knowledge sharing, learning organization and work life balance toward employee performance. This study was associative research and using quantitative method. The population in this study was the employees of palm oil industry, in which 110 of them are re-spondents and sample was taken by using simple random sampling. The data was collected through ques-tionnaire between July-December 2020 and we did validity test, reliability test, and classic assumption test before being analyzed by using multiple regression analysis. The result shows that knowledge sharing, learning organization and work life balance has significant impact, partially and simultaneously, toward employee performance. Managerial implication of this study was asking employees to be more proactive in doing task or project and also making collaborative job in order to make employee cooperate with their coworker well.